Kenya Nutrition Conversion Table (Kenya_NCT) - Custodio, Estefania (2025)
In order to estimate the nutrients intake from the food consumption module of the 2015/2016 Kenya Integrated Household Budget Survey (KIHBS), each of the food items reported in that module is matched with a food item in the Food Composition Table (FCT) or Food Database (FDB) of choice, and nutrients composition are then compiled in what is called the nutrition conversion table (NCT).